Clinical Implications of Compounds Designed to Inhibit ECM‐Modifying Metalloproteinases. Issue 23 (15th September 2017) - Amar, Sabrina; Minond, Dmitriy; Fields, Gregg B.
Abstract: Remodeling of the extracellular matrix (ECM) is crucial in development and homeostasis, but also has a significant role in disease progression. Two metalloproteinase families, the matrix metalloproteinases (MMPs) and a disintegrin and metalloproteases (ADAMs), participate in the remodeling of the ECM, either directly or through the liberation of growth factors and cell surface receptors. The correlation of MMP and ADAM activity to a variety of diseases has instigated numerous drug development programs. However, broad‐based and Zn 2+ ‐chelating MMP and ADAM inhibitors have fared poorly in the clinic. Selective MMP and ADAM inhibitors have been described recently based on (a) antibodies or antibody fragments or (b) small molecules designed to take advantage of protease secondary binding sites (exosites) or allosteric sites. Clinical trials have been undertaken with several of these inhibitors, while others are in advanced pre‐clinical stages.